Pseudacteon notocaudatus and Pseudacteon obtusitus (Diptera: Phoridae), two new species of fire ant parasitoids from South America - Plowes, Robert M.; Folgarait, Patricia J.; Gilbert, Lawrence E. (Zootaxa, 2015)
Ongoing studies in South America of phorid flies of the genus Pseudacteon Coquillett 1907 have revealed two further new species in this genus that are described here: P. obtusitus and P. notocaudatus. Both species are parasitoids of Solenopsis (F.) fire ants.